The Impact and Strategy for Combating the Outbreak Covid-19 in Student - Endin Mujahidin; Bahagia Bahagia; Fachruddin Majeri Mangunjaya; Rimun Wibowo (Universitas Pahlawan Tuanku Tambusai, 2021)
This study aims to find the social impact, morals, and strategies for dealing with COVID-19 among students. Another goal is to find out the social, religious and psychological impact of COVID-19 on students at Ibn Khaldun University, Bogor. The research method approach uses a descriptive qualitative approach. Data were collected by in-depth interviews with the head of the student class. The sample was selected through a purposive technique. The results were carefully examined through triangulation. The results showed that students could not establish social relations between students and did not participate in campus social organizations. Another finding, the Covid-19 outbreak has an impact on student morals because online meetings are more difficult to foster student morals because teachers do not meet students. In addition, students experience various stresses due to piling tasks and online learning does not face various obstacles such as difficulty communicating with lecturers and not understanding the material. Students take various ways to overcome stress such as listening to favourite music, watching YouTube, playing games, getting enough rest, eating favourite foods such as eating meatballs, straightening intentions, and also strengthening worship and getting closer to God.